Expectativas del turista y la satisfacción de los usuario del Complejo Turístico Rock And Straw de la Parroquia Isla de Bejucal del cantón Baba - Aviles Vera, Zolanch Antonella (2020)
The development of the case study was carried out in the Isla de Bejucal parish of the Baba canton belonging to the Los Ríos Province, which has two attractions within the canton, such as the Rock and Straw tourist complex and the Boga tourist complex, therefore both are related to the study of user satisfaction due to staff who are not specialized in the area of tourism to offer good service since they cannot meet the expectations of tourists. Through constant training to the local employees, it will bring as a consequence the improvement of the service, which will allow the tourist to have a better vision of the complex. In addition, the facilities of the complex should be improved and maintained adequately to offer a better service, the price of access to the establishment should be evaluated and this will increase the influx of tourists, in order to create sources of jobs within the community.